2001
DOI: 10.1002/ajp.2
|View full text |Cite
|
Sign up to set email alerts
|

Demography and pedigree structure of an SPF colony of rhesus monkeys (Macaca mulatta)

Abstract: The SPF rhesus colony at the M.D. Anderson Cancer Center in Bastrop, Texas, was analyzed with the aim of determining the demographic and genetic effects of stringent selection for virus-free breeders, permanent quarantine, continued surveillance, and culling of animals that show evidence of viral infection. The analysis shows minimal effects on population viability and loss of genetic variability in comparison with the traditionally managed (non-SPF) portion of the population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…An additional 31 females were introduced in 1980, and four males were introduced in 1985. The colony was closed to further immigration in 1985 ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…An additional 31 females were introduced in 1980, and four males were introduced in 1985. The colony was closed to further immigration in 1985 ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, significant reductions in infant mortality are important indicators or markers for beneficial management practices. Although not specifically addressing infant mortality, the only previous study of mortality in relation to SPF status, carried out at a large rhesus breeding facility in Texas, found that crude mortality was significantly reduced in a breeding population of rhesus macaques post‐conversion to SPF status, compared with the same population prior to conversion to SPF status . In the same study, it was considered due to the selection of healthier animals for SPF colony establishment or more careful clinical management related to the SPF animal selection compared with conventional management practices.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic analysis plays a significant role in animal colony management, including assessment of the effectiveness of current management practices, and prediction of future population size and structure. Although there are many studies reporting demographic aspects, including infant mortality analysis in captive rhesus macaques , to date, only one published report has attempted to address these basic demographic parameters in SPF populations . Here, we report the results of a retrospective study of infant mortality in SPF rhesus macaques over a six‐year period, with comparison to non‐SPF rhesus macaques in separate but contemporary breeding populations at the CNPRC.…”
Section: Introductionmentioning
confidence: 99%